Menggagas Paradigma Baru Pendidikan Matematika Kontemporer - Mailizar Mailizar (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2011)
Mathematics education in our country is currently experiencing a paradigm shift. There was a strong anxiety and awareness, especially among policy makers, to renew mathematics education. The aim is that the learning of mathematics more meaningful for students and can provide adequate supplies of competence both to further study or for entering the workforce. This paper describes the new paradigm. The outline will be elaborated on some new approaches in learning mathematics, such as kontruktivis, contextual (contextual teaching and learning or CTL), and in particular will be described on realistic mathematics education approach (MEA).